RELATIONSHIPS BETWEEN CLASSROOM MANAGEMENT STYLES AND GRADE 8 ENGLISH STUDENTS’ PERFORMANCE IN ADDIS ABABA MIDDLE SCHOOLS: A QUANTITATIVE ANOVA STUDY - Tsegaye Mitiku Zewdie; Seime Kebede (English Education Department at FKIP Nommensen University, 2026)
This cross-sectional quantitative study examined the relationship between teachers’ instructional and behavioral management styles and students’ performance in the Grade 8 English examination in Addis Ababa, Ethiopia. The population comprised 252 government middle schools, from which 36 schools were selected using a systematic simple random sampling technique. 42 Grade 8 English teachers in the sampled schools were included. A comprehensive sampling technique was used in selecting the teachers. Data were collected through a demographic survey and the Behavior and Instructional Management Scale (BIMS; Cronbach’s α = 0.75). Students’ performance was measured using their English passing rates in the Primary School Leaving Examination. Descriptive statistics, one-way ANOVA, and Tukey HSD post hoc tests were conducted to examine differences in student performance across classroom management styles. Results revealed statistically significant differences in students’ passing rates across instructional management styles, F(2, 39) = 8.181, p = .001, η² = .31, and behavioral management styles, F(2, 39) = 7.756, p = .001, η² = .28. Tukey HSD analysis indicated that students taught by interventionist teachers outperformed those taught by non-interventionist teachers, while differences between interactionalist teachers and the other groups were not statistically significant. These findings suggest that structured, teacher-directed classroom management styles are associated with higher student achievement in Grade 8 English.